MANAGEMENT IN THE FRENCH SYSTEM OF POLICE EDUCATION ON THE EXAMPLE OF FRANCE’S NATIONAL POLICE COLLEGE – OUTLINE OF ISSUES - Jacek Dworzecki (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The aim of the study is presentation of the French system of police education on the example of its central academic institution - France’s National Police College. The paper describes the management system of the College, recruitment procedures in the French National Police as well as forms of education and professional training offered by the police training centres in France. In the introduction to the main body of the paper, the reader will find detailed description of the central organisation unit of the French Police i.e. the General Directorate of the National Police with headquarters in Paris.